Modernism, nationalism, and the novel - Lewis, Pericles (Cambridge University Press, 2000)
"In Modernism, Nationalism, and the Novel Pericles Lewis shows how political debates over the sources and nature of "national character" prompted radical experiments in narrative form amongst modernist writers. Though critics have accused the modern novel of shunning the external world, Lewis suggests that, far from abandoning nineteenth-century realists' concerns with politics, the modernists used this emphasis on individual consciousness to address the distinctively political ways in which the modern nation-state shapes the psyche of its subjects. Tracing this theme through Joyce, Proust, and Conrad, amongst others, Lewis claims that modern novelists gave life to a whole generation of narrators who forged new social realities in their own images. Their literary techniques - multiple narrators, transcriptions of consciousness, involuntary memory, and arcane symbolism - focused attention on the shaping of the individual by the nation and on the potential of the individual, in time of crisis, to redeem the nation."--Jacket